Characterization of a Clostridioides difficile ST-293 isolate from a recurrent infection in Argentina - Soldavini Pelichotti, Paola Cecilia (2023)
Clostridioides difficile is an opportunistic spore-forming pathogen responsible for antibiotic-associated diarrhea in humans. C. difficile produces two main toxins: TcdA and TcdB as well as a third toxin named binary toxin (CDT) that is also involved in virulence. The present study aimed at characterizing the C. difficile isolate ALCD3 involved in a relapse episode of nosocomial infection. Molecular characterization showed that isolate ALCD3 belongs to toxinotype 0/v and the MLST analysis demonstrated allelic profile adk:91, atpA:1, dxr:2, glyA: 1, recA:27, sodA: 1 and tpi:1 which corresponds to ST293 (MLST clade: 1). During growth, isolate ALCD3 showed an early increase in the sporulation ratio as well as maximal values of heat resistant forms after 2 days of incubation. Both sporulation kinetics and production of heat resistant forms were faster for isolate ALCD3 than for the reference strain VPI 10463. Germination in the presence of the natural germinant taurocholate was faster for isolate ALCD3 than for strain VPI 10463, which indicates that isolate ALCD3 starts cortex hydrolysis earlier than strain VPI 10463. Furthermore, the co-germinant glycine, induces rapid release of dipicolinic acid (DPA) in isolate ALCD3. These findings indicate that isolate ALCD3 is particularly efficient in both sporulation and germination. The present work represents the first report of the circulation of C. difficile ST293 in Argentina. The ability of isolate ALCD3 to produce toxins and its high sporulation/germination capacity are key features compatible with a microorganism with high dissemination potential and the possibility of inducing recurrent infections.